1983
DOI: 10.1063/1.331831
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of corona-discharge photoionization sources for CO2 lasers

Abstract: The results of an experimental study of ultraviolet photoionization produced by a corona discharge in CO2 laser gases are reported. The influence of corona discharge physical and electrical parameters on the produced photoelectron density is investigated so that an optimized design of these types of photoionization sources can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Dashuk et al [10] reported that the negative streamer propagation velocity is larger than the positive, Murooka and Koyama [16] noted that exactly the opposite has been observed. Zaroslov et al [17] reported that the intensity of radiation emitted from dielectric species was in some cases ten times higher for a negative polarity surface discharge while in the work of Marchetti et al [18], where the efficiency of the sliding discharge as a preionization source for CO 2 lasers was investigated, the number of photoelectrons and hence of hard UV radiation was found to be three times larger in the case of positive polarity.…”
Section: Discussionmentioning
confidence: 97%
“…Dashuk et al [10] reported that the negative streamer propagation velocity is larger than the positive, Murooka and Koyama [16] noted that exactly the opposite has been observed. Zaroslov et al [17] reported that the intensity of radiation emitted from dielectric species was in some cases ten times higher for a negative polarity surface discharge while in the work of Marchetti et al [18], where the efficiency of the sliding discharge as a preionization source for CO 2 lasers was investigated, the number of photoelectrons and hence of hard UV radiation was found to be three times larger in the case of positive polarity.…”
Section: Discussionmentioning
confidence: 97%
“…By adjusting the length of the path between the electrodes and the field strength the surface discharge can be made self terminating due to the high electron losses because of recombination near the surface. It has been found experimentally, [1], that the production of UV radiation and therefore the electron density in the main discharge region increases with the magnitude of the displacement current. Also, the wavelength of the emitted UV radiation can be influenced by the energy of the corona discharge electrons.…”
mentioning
confidence: 97%
“…Also, the wavelength of the emitted UV radiation can be influenced by the energy of the corona discharge electrons. A higher electric field has been observed to produce shorter wave length W radiation and higher electron density in the main discharge region [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations